Idéias de liberdade na cena política capixaba: o movimento abolicionista em Vitória (1869/1888) - Pícoli, Mariana de Almeida (2009)
This thesis aimed to promote the campaign history ransom antislavery developed in Vitória, capital of the province of the Espírito Santo. The survey sought to identify the media used for the dissemination of propaganda abolitionist and emancipationist and the main creators of the movement carried out here. The campaign antislavery developed nationally, the political game between conservatives and liberals and coherence between the entry made in cutting – mainly-and the activities promoted by from Espírito Santo for redemption of slaves correspond to questions raised by this study. The period covered by the search, which started in 1869, is due to the inauguration of the first liberating association founded in Vitória, the Sociedade Abolicionista do Espírito Santo. This organization emancipationist foundation, for this study, represented a milestone of the campaign antislavery in Vitória. The year end of the abolitionist movement through the adoption of the law of the abolition of 1888 as configured deadline this dissertation. Journals: Jornal da Victoria, Correio da Victoria, O Espírito Santense e, A Província do Espírito Santo, served as sources this search. Printed chosen were due to the longevity of your publications. The predominance of one, or another, in political arena as announcer of enactments, reflected the political game in force in that period. Thus, through the analysis of the articles of its chosen writers and transcripts to compose the journalistic scope, you can diagnose shared political culture capixaba society. The results show that, despite the affinities with nationally developed antislavery movement, in the campaign presented moderate character in its activities. Compared to invested emancipationists and abolitionists held in São Paulo, in Ceará, in Rio de Janeiro and in other provinces, realized in Vitória some resistance to slavery relations radicalization reformation.